PENGEMBANGAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL TERINTEGRASI KARAKTER MATERI GAYA DALAM KEHIDUPAN SEHARI- HARI PADA SISWA KELAS IV SEKOLAH DASAR - Tri Astuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to: (1) produce a digital comic based on local wisdom integratedwith characters, specifically on the topic of style in everyday life for fourth-gradeelementary school students; (2) determine the feasibility of the developed digitalcomic product based on validation results from material experts and mediaexperts, as well as responses from teachers and students.Product development uses the ADDIE model, which includes the stages ofanalysis, design, development, implementation, and evaluation. Assessmentinstruments include validation sheets, teacher and student responsequestionnaires, and learning outcome tests. The study subject was fourth-gradestudents of Pringgowijayan State Elementary School, with 18 students as subjects.Trials were conducted on a limited basis with 5 students and on a broader basiswith 13 students.The media expert validation results showed a percentage of 93% and the materialexpert validation reached 97%, both in the very valid category. Practicality basedon the teacher response questionnaire obtained a percentage of 95% and studentresponses of 88.75% (limited trial) and 93.5% (wide trial), with the category of verypractical. The effectiveness of digital comics on student learning outcomesdemonstrated a classical mastery score of 89%, meeting the criteria for highlyeffective. Thus, digital comics based on local wisdom and integrated charactersare deemed feasible, highly practical, and effective as learning media forimproving students' understanding and character in fourth-grade science lessons.This product is recommended for implementation in elementary schools as aninnovative and contextual alternative instructional media.